Differentiation of lymphoid cells: the non-mitogenic induction of immunoglobulin production by thymus cell extract and thymus cell culture filtrate. - Shinohara, N (1976)
The cell-free medium in which thymocytes have been cultured (filtrate) as well as sonic lysates of thymocytes (extract) enhance immunoglobulin production when added to spleen cells during tissue culture. In spite of the requirement for foetal calf serum in the culture medium, production of the enhancing factor in thymocyte culture filtrates occurred even in the presence of a variety of metabolic inhibitors including NaN3, puromycin and hydroxyurea. Although DNA synthesis is required as a prelude to the induction of immunoglobulin production, two lines of evidence indicate that the enhancement produced in response to filtrate and extract occurs via a non-mitogenic process. First, neither cell-free agent was mitogenic toward spleen cells. Secondly, the enhancement of immunoglobulin production due to filtrate or extract was observed even in the presence of inhibitors of DNA synthesis. Multiple functions for thymocytes in the induction of immunoglobulin production are indicated by the findings that thymocytes restore immunoglobulin production of anti-thymocyte serum-treated spleen cells, whereas filtrate and extract, alone or in combination, do not have this capability. Furthermore, filtrate and extract failed to enhance the induction of DNP-group-specific antibody production by cells incubated with DNP-protein, but filtrate and extract could partially restore anti-DNP antibody production of such anti-thymocyte serum-treated cells. The role of thymocytes, filtrate and extract in the antigen-independent and the antigen-dependent induction of immunoglobulin production is discussed.